Review of gynecological-obstetric violence from current regulation and legislative proposals: a comparative study - Palomares Herrera, Manuel (Universidad Hemisferios, 2025)
The absence of doctrinal research on gynecological-obstetric violence is at the same level as its advance in the Administration, or at least with different speeds between States. Therefore, in this study we present how it is currently regulated in Spain and in several Latin American countries, which jurisprudential digest is developing its new issues and how a special florilege is being projected for a subject that is still in a primitive phase in parliamentary spheres but effervescent. in the professional debate in the healthcare union, patient associations and jurists in the healthcare sector.